Giant pandas - Gibbons, Gail. (New York : Scholastic, 2002)
An introduction to the physical characteristics, behavior, life cycle, and habitat of these endangered animals.
G7
Keywords: Giant panda -- Juvenile literature; Giant panda; Pandas; Endangered species